2011
DOI: 10.1017/s104795111100182x
|View full text |Cite
|
Sign up to set email alerts
|

Right pulmonary artery to left atrial fistula: a description of two cases, emphasising a diagnostic approach

Abstract: Right pulmonary artery to left atrial fistula is a rare pathology characterised by a right to left shunt. Another important aspect of this pathology is the difficulty encountered in making a diagnosis, which is why the diagnosis is frequently delayed into adulthood. A description of two cases is used to emphasise the importance of the different modes of echocardiography as a diagnostic tool in diagnosis, as well as the two different clinical forms that it adopts: a group of patients suffering cardiac failure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Selective RPA angiography remains the most definitive investigation for confirmation and accurate imaging of this anomaly, but is invasive . We found that TTE was an effective, noninvasive, inexpensive, and reproducible diagnostic method . Of the 3 cases, 2 were diagnosed by TTE, and the other was misdiagnosed as a pulmonary arteriovenous fistula by contrast echocardiography.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Selective RPA angiography remains the most definitive investigation for confirmation and accurate imaging of this anomaly, but is invasive . We found that TTE was an effective, noninvasive, inexpensive, and reproducible diagnostic method . Of the 3 cases, 2 were diagnosed by TTE, and the other was misdiagnosed as a pulmonary arteriovenous fistula by contrast echocardiography.…”
Section: Discussionmentioning
confidence: 95%
“…9,18 We found that TTE was an effective, noninvasive, inexpensive, and reproducible diagnostic method. 13 Of the 3 cases, 2 were diagnosed by TTE, and the other was misdiagnosed as a pulmonary arteriovenous fistula by contrast echocardiography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Interestingly, when discussing direct fistulous connections with the left atrium, there is a strong male predominance estimated at 3:1. 3 The presentation can vary depending on the size of the shunt and can include exertional dyspnoea, cyanosis, cerebrovascular accidents, and systemic embolisation. 2,3 Studies including children and adults report an incidence of neurological events related to pulmonary arteriovenous fistula as 37% for transient ischaemic attacks and 18% for stroke.…”
mentioning
confidence: 99%
“…3 The presentation can vary depending on the size of the shunt and can include exertional dyspnoea, cyanosis, cerebrovascular accidents, and systemic embolisation. 2,3 Studies including children and adults report an incidence of neurological events related to pulmonary arteriovenous fistula as 37% for transient ischaemic attacks and 18% for stroke. 4 Systemic, non-cerebral embolisms account for 5-10% of all paradoxical events; however, recent studies demonstrate that this is a rare occurrence, even in patients with hypercoagulopathy.…”
mentioning
confidence: 99%